Studying The Extrusion Process Of A Sintered Thin-Wall Pipe Loaded With Internal High Pressure In Case Of A Boundary Condition In The Die Inlet - Babayan, A. A. («Պոլիտեխնիկ» տպ.)
An analytical study of the process of sintered thin-wall pipe extrusion loaded with internal high pressure, on its cross section in the conical die inlet by compressing meridional dimensionless stress has been carried out. It is assumed that the external die pressure Pv and the internal high pressure Pr acting on the pipe are equal. In this case, the circumferential stress is determined and a simplified plasticity condition is obtained. The dimensionless values of meridional, circumferential and average stresses depending on the degree of pipe deformation were determined, which made it possible to study the processes of their compaction using the DTPPM equations at different values of coefficients of friction and initial porosities of the pipe material. Կատարվել է ներքին բարձր ճնշումով բեռնավորված եռակալված խողովակի կոնական մամլամայրում մամլման գործընթացի հետազոտում` վերլուծական մեթոդով, դրա մամլամայր մտնող վերին լայնական հատույթին սեղմող միջօրեական լարում կիրառելով։ Ենթադրվում է, որ խողովակի վրա ազդող մամլամայրի հպակային Pv և դրա ներսում ազդող Pr ճնշումները հավասար են: Այդ դեպքում որոշվում է խողովակի շրջանային լարումը, և ստացվում է պարզեցված պլաստիկության պայման: Որոշվել են խողովակի դեֆորմացման աստիճանից կախված միջօրեական, շրջանային և միջին լարումների չափազուրկ մեծությունները, որոնք հնարավորություն են տվել, օգտագործելով ծակոտկեն նյութերի պլաստիկության դեֆորմացիոն տեսության բանաձևերը, տարբեր շփման գործակիցների և խողովակի նյութի սկզբնական ծակոտկենության դեպքերում ուսումնասիրել դրանց խտացման գործընթացը: Проведено аналитическое исследование процесса экструзии спеченной тонкостенной трубы, нагруженной внутренним высоким давлением, при входе в коническую матрицу с использованием сжимающего меридионального безразмерного напряжения на ее поперечном сечении. Предполагается, что действующие на трубу внешнее давление матрицы Pv и внутреннее высокое давление Pr равны. В этом случае определяется окружное напряжение и получается упрощенное условие пластичности. Определены безразмерные величины меридиональных, окружных и средних напряжений в зависимости от степени деформации трубы, которые позволили с использованием уравнений деформационной теории пластичности пористых материалов при различ- ных значениях коэффициентов трения и начальных пористостей материала труб изучить процессы их уплотнения.
Keywords: Mechanical engineering